Oral Presentations Abstracts: BLIND SPOTS RECONSIDERED – EPISTEMIC INJUSTICE IN CLINICAL ETHICS SUPPORT - MUFF, Aurora; HANG LE, Thu; BUZZI, Michael; PORZ, Rouven (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Conducting ethical case discussions is a core aspect of any clinical ethics support service or work as an ethical consultant in a hospital. Numerous case discussion methods can be used to do this, many of which are based on Beauchamp and Childress’ four biomedical principles. Other commonly used types are the ‘moral case deliberations’ by prominent authors such as Widdershoven, Molewijk et al. However, based on our practical work as clinical ethicists, and doctoral students in the field of clinical ethics, we would like to hypothesize that most of the methods seem to be in need of philosophical supplementation, especially on the blind spots regarding the is-ought fallacy, i.e. how to relate empirical data to normative conclusions. A further weakness may be found in the inadequate handling of power structures, which may lead to an unjust handling of opinions. In our talk, we will therefore present Miranda Fricker’s conceptual idea of ‘epistemic injustice’ and we will apply these insights to clinical cases of our everyday practice. Epistemic injustice is injustice related to knowledge. The concept focuses on exclusion and silencing people in public discourse. This silencing leads to a systematic distortion or misrepresentation of one’s meanings or contributions and/or to an undervaluing of someone’s status in communicative practices. We think that this concept has not been considered in clinical ethics thus far, and we would like to discuss whether ethical case discussions should not help to avoid epistemic injustice. If so, then the case discussion methods of our discipline should be adapted accordingly.